2011
DOI: 10.1182/blood-2011-02-334821
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-refractory GVHD: T-cell attack within a vulnerable endothelial system

Abstract: Acute graft-versus-host disease (GVHD) is a major complication of allogeneic stem cell transplantation (SCT) and can be readily controlled by systemic high-dose steroids in many patients. However, patients whose GVHD is refractory to this therapy have a poor prognosis. Refractory patients have ongoing end-organ damage despite effective immunosuppression with second-line regimens, suggesting pathomechanisms independent from the initiating T-cell attack. To explore whether endothelial damage might contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
164
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(174 citation statements)
references
References 30 publications
(51 reference statements)
10
164
0
Order By: Relevance
“…Unfortunately, neither did they analyze pediatric patients separately nor state whether Ang2 was analyzed from plasma or serum. In a recent study of Luft et al,20 Ang2/VEGF was associated with steroid-refractory GVHD. According to their study, endothelial cell vulnerability and dysfunction, rather than refractory T-cell activity, drives treatment refractoriness of GVHD via Ang2, VEGF and thrombomodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, neither did they analyze pediatric patients separately nor state whether Ang2 was analyzed from plasma or serum. In a recent study of Luft et al,20 Ang2/VEGF was associated with steroid-refractory GVHD. According to their study, endothelial cell vulnerability and dysfunction, rather than refractory T-cell activity, drives treatment refractoriness of GVHD via Ang2, VEGF and thrombomodulin.…”
Section: Discussionmentioning
confidence: 99%
“…6 Along with this, there are multiple studies that examine endothelial activation markers in the post-BMT period including von Willebrand factor, thrombomodulin and Fas/Fas-ligand. 5,7,8 The mounting evidence of angiopathy associated with GvHD and BMT is even further displayed with more qualitative analysis of structural findings including vessel rarefication, neovascularization, endothelial microparticles and circulating endothelial cells. 5,[8][9][10] While the research demonstrates potential vascular damage directly associated with GvHD, the question as to a relationship to poor wound healing has received little to no attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that vascular endothelial vulnerability and endothelial dysfunction are involved in the pathogenesis of GVHD. [11][12][13] Elevated pretransplant serum levels of angiopoietin-2, a hormone mediating vascular vulnerability, and nitrate are noted in steroidrefractory GVHD patients. 11,12 A marker of endothelial damage including soluble TM is elevated in patients with steroid-refractory GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Elevated pretransplant serum levels of angiopoietin-2, a hormone mediating vascular vulnerability, and nitrate are noted in steroidrefractory GVHD patients. 11,12 A marker of endothelial damage including soluble TM is elevated in patients with steroid-refractory GVHD. 13 These observations encouraged us to hypothesize that the prophylactic use of rTM with cytoprotective as well as antiinflammatory activity would decrease the incidence of GVHD in transplant patients.…”
Section: Introductionmentioning
confidence: 99%